Global pazarlamada küçük- ortaboy işletmelerin rekabet gücü araştırması ve bir uygulama - Şen, Zeynel (My University, 2002)
Bu çalışma Küçük ve Orta Boy İşletmelerin ihracatta organizasyon modeli olan sektörel Dış Ticaret Şirketlerinin bir değerlendirilmesi olarak başlamıştır. Tezin amacı global pazarlarda rekabetçi üstünlükleri ve avantajları olan KOBİ'leri değerlendirmek ve mevcut modelde eksik olan yönleri tespit ederek ülkemizdeki KOBİ'lere uygun ihracat evlerinin alt yapısını oluşturmaktır. Çalışma dört bölüm halinde yapılmıştır. Birinci bölümde global pazarlar hakkında verilmiş, global pazarlamadaki gelişmeler değerlendirilmiştir. Bu pazardaki rekabetçi avantajlar belirtilmiştir. Global rekabet gücü faktörleri ve KOBİ'lerin rekabet gücü ortaya çıkartılmıştır. Dünya ülkelerindeki KOBİ'lerin yeri tesbit edilmiştir. İkinci bölümde bu konuda teorik yaklaşımlar ele alınmıştır. İhracata etki eden güçler, ihracatta üstünlükler değerlendirilerek KOBİ'lerin avantajlı olduğu yönleri bir bütünlük içinde açıklanmıştır. KOBİ'ler bu bağlamda yeni yüzyılın ihracatçı üstünlükleri olan ve ihracat pazarlamasında avantajları bulunan firmalar olarak gündeme gelmektedir. Üçüncü bölümde Türkiye de uygulanmakta olan KOBİ ihracat organizasyonu Sektörel Dış Ticaret Şirketleriüzerinde bir araştırma yapılmış,bu modelin aksayan yönleri belirlenerek yeni ihracat evleri modeli sisteme ilave edilmiştir.böylece ülkemiz KOBİ'lerinin uluslararası pazarlarda rekabetçi hale gelebilmeleri için doğru ve uygun örgütlenmenin gereği vurgulanmıştır. Son bölümde çalışma bir bütün olarak değerlendirilerek mevcut sistemin aksıyan yönleri gösterilerek çözüm önerileri sunulmuştur.Batı ülkelerinde uzun zamandır uygulanmakta olan ihracat evleri modelin içine dahil edilmiştir.Böylece KOBİ'lerin pazarlama,satış,pazar araştırması, pazarlama yönetimi ve uluslararası düzende entegrasyonlarını yapacak bir üst örgütlenme modeli ihtiyacı ortaya çıkmıştır.Bunun için global pazarlama faktörleri göz önüne alınarak çözüm önerileri sunulmuştur.

The purpose of this study can be evaluated as an export infrustructure of Small and Medium Sized Business (SME's) in Turkey. The thesis is studied on Small and Medium Sized Business in Global Marketing in Turkey, SME's power of export competition and export advantage has been evaluated under the SME's export system as it is applied now. The Sectoral Foreign Trade System also has been evaluated. The study is composed of four chapters. In the first chapter, general information about of Global Marketing is given and also SME's export powers have been evaluated in the global marketing. The powers of export competition factors whinch are the flow of changing in Global Marketing in a new century. In the second chapter, the effects of power of export and export advantage and disadvantage of SME's have also been examined. The theories of global marketing advantage have been investigated thoroughly. Although SME's in Turkey and in the world have many problems, they have also most export advantage of all. The new export competent and new abilities of SME's have became very important. In according to authorize their advantages are more than large business. Although the SME's ability, dynamic and flexible capacity these abilities are not used properly. In the third chapter, export modeling in Turkey on the SME's has been examined, In Turkey, SME's export has been organized under the Sectoral Foreign Trade Companies this model didn't use effectively and has not bean effected by many factors. In the world size, the most important role of SME's is the Foreign Export Trade. The Sectoral Foreign Trade Companies model is not enough to have export for SME's and Export Capacity of SME's. this model can not be used in Turkey properly. This model should be improved. Smilar to this model is Export House that can be used in western countries. If this Export House model has been advanced, SME's in Turkey will be gained much power of export. In addition, this model ofter many kinds of organization type for SME's. In the last chapter. The study has been appraised. SME's roles in the economy are vital. As a result we have to change Sectoral Foreign Trade Modeling in order to support for SME's. In addition to, the government must understand SME's export power of worth. As a result, we offer a new model of export of export houses. This system not only provides sales, administration, marketing, marketing research and export information, but also considerably contributes to support countrywide economy in large scale and SME's.
Keywords: Küçük Ve Orta Işletmeler; Pazarlama; Rekabet Türkiye